Implications of S1 tephra findings in Dead Sea and Tayma palaeolake sediments for marine reservoir age estimation and palaeoclimate synchronisation - Neugebauer, Ina; Wulf, Sabine (Quaternary science reviews, 2017)
Here we report on the first findings of a cryptotephra in the Holocene lacustrine sediment records of the Dead Sea and Tayma palaeolake (NW Arabian Peninsula). The major element glass composition of this rhyolitic tephra is identical to the distal ‘S1’ tephra layer identified in the Yammoûneh palaeolake (Lebanon), in a marine sediment record from the SE Levantine basin and in the Sodmein Cave archaeological site in Egypt. The S1 tephra corresponds to the early Holocene ‘Dikkartın’ dome eruption of the Erciyes Dağ volcano in central Anatolia (Turkey) and has been dated in the marine record at 8830 ± 140 cal yr BP. We present new age estimates of the S1 tephra based on radiocarbon dating of terrestrial plant remains and pollen concentrates revealing ages of 8939 ± 83 cal yr BP in the Dead Sea sediments and 9041 ± 254 cal yr BP in Tayma. The precise date from the Dead Sea allows refining the early Holocene marine reservoir age in the SE Levantine Sea to ca. 320 ± 50 years. Synchronisation of marine and terrestrial palaeoclimate records in the eastern Mediterranean region using the S1 tephra further suggests a time-transgressive expansion of the early Holocene humid period.
Available online 28 June 2017
Gesehen am 18.06.2018